Studi In Silico Senyawa Cendawan Endofit Sebagai Kandidat Obat Antiangiogenesis Hemangioma - Masriany Masriany; Risman Rifaldi; Eka Sukmawaty (Institut Pertanian Bogor, 2022)
Increasing levels of angiogenic factors such as gamma interferon (Y-IF), tumor necrosis factor-beta (TNF-β), and transforming growth factor-beta (TGF-β) are thought to be the cause of the angiogenesis process in hemangiomas. Endophytic fungi are potential in searching for new drug sources due to their antimicrobial, antifungal, and anticancer compounds. This study aimed to determine the potential and interactions of endophytic fungi as candidates for vascular endothelial growth factor receptor-2 (VEGFR-2) angiogenesis hemangiomas and apply Lipinski's rule of five to differentiate drug-like and non-drug-like molecules and in-line toxicity using in silico test. The research method was molecular docking using several programs, namely Autodock Vina (PyRx), PyMol, and Discovery Studio 2019, and tethering five ligands from the endophytic fungus Trichoderma sp. and Aspergillus sp. with 2 VEGFR-2 target proteins (protein codes were 3VHE and 1Y6A). The best binding affinity of the ligands was tested by Lipinski's rule of five and toxicity test using Toxtree. The results showed that benzyl benzoate is potentially an antiangiogenesis inhibitor for VEGFR-2 protein based on its binding affinity value, which is close to the control ligand value of -8.7 kcal/mol (3VHE) and -7.4 kcal/mol (1Y6A). Therefore, benzyl benzoate, chloromycetin, and 1-hexyl-3-nitrobenzene compounds comply with Lipinski's rule of five. Based on the results of the toxicity test and the parameters of the Kroes TTC decision tree, benzyl benzoate and chloromycetin are categorized as safe compounds for consumption. Keywords: angiogenesis, benzyl benzoate, endophytic fungi, molecular docking, VEGFR-2